Synthesis of 3(2)-phosphonylated thiazolo[3,2-a]oxopyrimidines - Kaskevich, Ksenia I.; Babushkina, Anastasia A.; Gurzhiy, Vladislav V.; Egorov, Dmitrij M.; Svintsitskaya, Nataly I.; Dogadina, Albina V. (Beilstein Journal of Organic Chemistry, 2020)
A series of 3(2)-phosphonylated thiazolo[3,2-a]oxopyrimidines was synthesized for the first time by the reactions of chloroethynylphosphonates with unsubstituted and 5(6)-substituted 2-thiouracils. The reaction of chloroethynylphosphonates with 6-substituted 2-thiouracils bearing electron-donor groups (CH3, Ph) proceeded with high regioselectivity involving the cyclization through the N3-nitrogen atom to form new 3-phosphonylated thiazolo[3,2-a]-5-oxopyrimidines with good yield. In the case of unsubstituted and 5-methyl-2-thiouracils, cyclization occurred predominantly through the N1 atom and partially via the N3-nitrogen atom to form a mixture of the corresponding thiazolo[3,2-a]-7- and 5-oxopyrimidines. A dramatic change in the reaction regioselectivity was observed in the case of 6-trifluoromethyl-2-thiouracil that afforded 2- and 3-phosphonylated 5-oxothiazolopyrimidines in a 1:1 ratio.
Keywords: chloroethynylphosphonate; heterocyclization; phosphonylated thiazolopyrimidines; phosphonylation; thiazolopyrimidine; 2-thiouracil

(untitled) - Awad, S. M.; Youns, M. M.; Ahmed, N. M. (Pharmacophore, 2018)

(untitled) - Cui, P.; Li, X.; Zhu, M.; Wang, B.; Liu, J.; Chen, H. (Bioorg. Med. Chem. Lett., 2017)

(untitled) - Ahmed, N. M.; Mohamed, M. S. (J. Adv. Pharm. Res., 2017)

(untitled) - Shin, N.; Li, Y.-L.; Mei, S.; Wang, K. H.; Hall, L.; Katiyar, K.; Wang, Q.; Yang, G.; Rumberger, B.; Leffet, L.; He, X.; Rupar, M.; et al. (J. Pharmacol. Exp. Ther., 2018)

(untitled) - Abdo, N. Y. M. (Acta Chim. Slov., 2015)

(untitled) - Khobragade, C. N.; Bodade, R. G.; Konda, S. G.; Dawane, B. S.; Manwar, A. V. (Eur. J. Med. Chem., 2010)

(untitled) - Mohamed, M. M.; Khalil, A. K.; Abbass, E. M.; El-Naggar, A. M. (Synth. Commun., 2017)

(untitled) - El-Borai, M. A.; Rizk, H. F.; Ibrahim, S. A.; El-Sayed, H. F. (J. Heterocycl. Chem., 2017)

(untitled) - Banothu, J.; Khanapur, M.; Basavoju, S.; Bavantula, R.; Narra, M.; Abbagani, S. (RSC Adv., 2014)

(untitled) - Ravendra Babu, K.; Koteswara Rao, V.; Nanda Kumar, Y.; Polireddy, K.; Venkata Subbaiah, K.; Bhaskar, M.; Lokanatha, V.; Naga Raju, C. (Antiviral Res., 2012)

(untitled) - Mohamed, S. F.; Flefel, E. M.; Amr, A. E.-G. E.; Abd El-Shafy, D. N. (Eur. J. Med. Chem., 2010)

(untitled) - Jeanneau-Nicolle, E.; Benoit-Guyod, M.; Namil, A.; Leclerc, G. (Eur. J. Med. Chem., 1992)

(untitled) - Jeanneau-Nicolle, E.; Benoit-Guyod, M.; Leclerc, G. (Synth. Commun., 1991)

(untitled) - Awadallah, F. M. (Sci. Pharm., 2008)

(untitled) - Veretennikov, E. A.; Pavlov, A. V. (Russ. J. Org. Chem., 2013)

(untitled) - Yaragatti, N. B.; Kulkarni, M. V.; Ghate, M. D.; Hebbar, S. S.; Hegde, G. R. (J. Sulfur Chem., 2010)

(untitled) - Abdel-fattah, A.-S. M.; Negm, A. M.; Gaafar, A. E. M. (Phosphorus, Sulfur Silicon Relat. Elem., 1992)

(untitled) - Frolova, T. V.; Kim, D. G.; Sharutin, V. V.; Shal’kova, E. N. (Russ. J. Org. Chem., 2016)

(untitled) - Mohamed, K. S.; Abdulaziz, N. M.; Fadda, A. A. (J. Heterocycl. Chem., 2013)

(untitled) - Elokhina, V. N.; Nakhmanovich, A. S.; Stepanova, Z. V.; Lopyrev, V. A.; Bannikova, O. B.; Struchkov, Y. T.; Shishkin, O. V. (Russ. Chem. Bull., 1996)

(untitled) - El-Emary, T. I.; Abdel-Mohsen, S. A. (Phosphorus, Sulfur Silicon Relat. Elem., 2006)

(untitled) - Lukáč, M.; Hocková, D.; Keough, D. T.; Guddat, L. W.; Janeba, Z. (Tetrahedron, 2017)

(untitled) - Abdou, W. M.; Barghash, R. F.; Khidre, R. E. (Monatsh. Chem., 2013)

(untitled) - Modranka, J.; Jakubowski, R.; Janecki, T. (Synlett, 2014)

(untitled) - Abdou, W. M.; Shaddy, A. A.; Kamel, A. A. (Chem. Pap., 2017)

(untitled) - Abdou, W. M.; Barghash, R. F.; Bekheit, M. S. (Arch. Pharm. (Weinheim, Ger.), 2012)

(untitled) - Radi, S.; Lazrek, H. B. (J. Chem. Res., Miniprint, 2002)

(untitled) - Jansa, P.; Hradil, O.; Baszczyňski, O.; Dračínský, M.; Klepetářová, B.; Holý, A.; Balzarini, J.; Janeba, Z. (Tetrahedron, 2012)

(untitled) - Andrew, H. F.; Bradsher, C. K. (J. Heterocycl. Chem., 1967)

(untitled) - Attaby, F. A.; Eldin, S. M. (Z. Naturforsch., B: J. Chem. Sci., 1999)

(untitled) - Weng, Y. Y.; Ying, L. M.; Chen, Q. X.; Su, W. K. (Chin. Chem. Lett., 2012)

(untitled) - Keivanloo, A.; Bakherad, M.; Rajaei, M. (Phosphorus, Sulfur Silicon Relat. Elem., 2014)

(untitled) - Khudina, O. G.; Ivanova, A. E.; Burgart, Y. V.; Pervova, M. G.; Shatunova, T. V.; Borisevich, S. S.; Khursan, S. L.; Saloutin, V. I. (Russ. J. Org. Chem., 2019)

(untitled) - Althagafi, I.; El-Metwaly, N.; Farghaly, T. A. (Molecules, 2019)

(untitled) - Ramadan, S. K.; El-Helw, E. A. E.; Sallam, H. A. (Heterocycl. Commun., 2019)

(untitled) - Morsy, H. A.; Moustafa, A. H. (J. Iran. Chem. Soc., 2020)

(untitled) - Krylov, A. S.; Kaskevich, K. I.; Erkhitueva, E. B.; Svintsitskaya, N. I.; Dogadina, A. V. (Tetrahedron Lett., 2018)

(untitled) - Erkhitueva, E. B.; Panikorovskii, T. L.; Svintsitskaya, N. I.; Trifonov, R. E.; Dogadina, A. V. (Synlett, 2018)

(untitled) - Krylov, A. S.; Petrosian, A. A.; Piterskaya, J. L.; Svintsitskaya, N. I.; Dogadina, A. V. (Beilstein J. Org. Chem., 2019)

(untitled) - Xu, H.; Zhang, Y.; Huang, J.; Chen, W. (Org. Lett., 2010)

(untitled) - Erkhitueva, E. B.; Dogadina, A. V.; Khramchikhin, A. V.; Ionin, B. I. (Tetrahedron Lett., 2012)

(untitled) - Mehta, S.; Larock, R. C. (J. Org. Chem., 2010)

(untitled) - Cho, C.-H.; Neuenswander, B.; Larock, R. C. (J. Comb. Chem., 2010)

(untitled) - Kolli, S. K.; Nakhi, A.; Medishetti, R.; Yellanki, S.; Kulkarni, P.; Ramesh Raju, R.; Pal, M. (Bioorg. Med. Chem. Lett., 2014)

(untitled) - Sanz, R.; Guilarte, V.; Hernando, E.; Sanjuán, A. M. (J. Org. Chem., 2010)

(untitled) - Kashiki, T.; Shinamura, S.; Kohara, M.; Miyazaki, E.; Takimiya, K.; Ikeda, M.; Kuwabara, H. (Org. Lett., 2009)